Game Based Learning With Local Wisdom: Developing A Snakes And Ladders Media For Folklore Education In Elementary Schools - Nurul Aswar; Sulastri Sulastri; Sukirman Sukirman (Journal of Innovation and Research in Primary Education, 2026)
This study aimed to develop and evaluate the feasibility of a Snakes and Ladders learning medium integrating the Sawerigading folktale and local wisdom values for fifth-grade folklore instruction in Indonesian elementary schools. A Research and Development (R&D) design guided by the ADDIE model was employed, with one classroom teacher and 18 fifth-grade students at SDN 269 Lambatu, East Luwu Regency, as research subjects, selected through purposive sampling. Data were collected via observation, semi-structured interviews, questionnaires, and documentation, and analyzed using a mixed-methods approach. Needs analysis revealed that 100% of students preferred game-based learning, while teachers reported overreliance on conventional textbook-based instruction. The developed medium incorporated 36 game squares embedding comprehension questions and cultural reflection tasks drawn from the Sawerigading narrative. Expert validation yielded scores of 82.50% (media), 83.33% (content), and 80.00% (cultural), all within the valid to very valid category. Practicality testing produced scores of 91.56% from students and 91.66% from the teacher, both classified as very practical. These findings confirm that traditional game mechanics and regional folklore can be systematically synthesized into a culturally coherent and pedagogically sound instructional medium. This study contributes a replicable, ADDIE-based model for culturally responsive learning media development applicable across diverse regional contexts in Indonesia.